Elucidation of mechanisms underlying active oxygen burst in Citrus sinensis after Diaporthe citri infection using transcriptome analysis - Liu, Tiantian; Zhou, Zehua; Luo, Changwei; Luo, Hua; Tang, Jun; Shi, Xiaojiang; Li, Diping; Zhang, Qiong; Li, Jin; Xia, Yonggang; Song, Na; Yi, Tuyong (Frontiers in Microbiology, 2024)
Introduction: Reactive oxygen species (ROS) generation is a common disease defense mechanism in plants. However, it is unclear whether Citrus host activates defense response against Diaporthe citri causing citrus melanose disease by producing ROS, and the underlying molecular mechanisms are unknown. Methods: DAB staining and RNA-Seq technology were used to compare the active oxygen burst and differential gene expression, respectively, in uninfected and infected C. sinensis leaves at different time points during D. citri infection in vivo. The functions of CsRBOH (a significant DEG) were confirmed in N. benthamiana through the Agrobacterium-mediated transient expression system. Results: DAB staining indicated that C. sinensis initiated defense against D. citri infection within 24 h by generating ROS. Illumina sequencing revealed 25,557 expressed genes of C. sinensis. The most upregulated DEGs (n = 1570) were identified 72 h after fungal inoculation (sample denoted as CD72). In the CD72 vs Cs (samples at 0 h after fungal inoculation) comparison, the KEGG pathway category with the highest number of genes (n = 62) and most significant enrichment was Protein processing in endoplasmic reticulum, followed by Glutathione metabolism and MAPK signaling pathway - plant. GO analysis revealed that the DEGs of CD72 vs Cs related to active oxygen burst and chitin recognition were significantly grouped into the regulation of biological processes and molecular functions, with GO terms including response to ROS, response to fungus, and oxidoreductase activity. Remarkably, CsRBOH was significantly enriched in the GO and KEGG analyses, and its expression pattern in qRT-PCR and DAB staining results were consistent. Among the 63 ROS-related DEGs, HSP genes and genes associated with the peroxidase family were highly significant as revealed by protein-protein interaction networks. Furthermore, ROS accumulation, cell death, and upregulation of defense-related genes were observed in N. benthamiana leaves with CsRBOH expressed through the Agrobacterium-mediated transient expression system. Conclusion: Our findings suggested that C. sinensis activates CsRBOH and ROS-related genes, leading to ROS accumulation to resist the invasion by D. citri. This study laid the foundation for future research on molecular mechanisms and breeding of C. sinensis cultivars resistant to citrus melanose.